1971
DOI: 10.1039/c29710001615
|View full text |Cite
|
Sign up to set email alerts
|

Cyanotrihydroborato- and tetrahydroborato-complexes of rhodium and iridium

Abstract: SumnznryThe synthesis and properties of air-stable hydroborato-complexes, trans-WA(C0) (R,P),] W = Ir, Rh; A = BH,(CN), BH,; R,P = tertiary phosphine] are reported ; the co-ordination of BH,(CN)-, probably through the -NC group, is the first example of this anion acting as a ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

1972
1972
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 0 publications
0
14
1
1
Order By: Relevance
“…trans-[Rh(NCBH 3 )(CO)(PPh 3 ) 2 ], (2). In contrast to the published two-stage procedure (Vaska et al, 1971), in the present work, we have found that (2) can be obtained easily from (1) in 77% yield by a metathesis reaction in methanol, i.e.…”
Section: Methodscontrasting
confidence: 99%
See 1 more Smart Citation
“…trans-[Rh(NCBH 3 )(CO)(PPh 3 ) 2 ], (2). In contrast to the published two-stage procedure (Vaska et al, 1971), in the present work, we have found that (2) can be obtained easily from (1) in 77% yield by a metathesis reaction in methanol, i.e.…”
Section: Methodscontrasting
confidence: 99%
“…The Vaska-type complexes trans-[RhX(CO)(PPh 3 ) 2 ] (X is a halogen or pseudohalogen) were extensively studied for many years due to their ability to undergo a range of reactions and their considerable catalytic activity (Roodt et al, 2003); the crystal structure of trans-[RhCl(CO)(PPh 3 ) 2 ], (1), was examined repeatedly (Ceriotti et al, 1983;Rheingold & Geib, 1987;Chaloner et al, 1991;Chen et al, 1991;Dunbar & Haefner, 1992;Kemp et al, 1995). The rhodium cyanotrihydridoborate complex trans-[Rh(NCBH 3 )(CO)(PPh 3 ) 2 ], (2), obtained from trans-[RhCl(CO)(PPh 3 ) 2 ], (1) (Vaska et al, 1971), has not been structurally characterized up to now, except for an IR spectroscopic analysis, although the syntheses and crystal structures of many cyanotrihydridoborate complexes of Group 6-8 transition metals have been reported, for example, [N(CH 3 ) 4 ] 3 [M(NCBH 3 ) 3 (CO) 3 ]ÁDME (M = Cr, Mo or W; DME = 1,2-dimethoxyethane), [N(CH 3 ) 4 ] 2 [Cr(NCBH 3 ) 2 (CO) 4 ] (Liu et al, 2004) and [M( 3 -C 3 H 5 )(NCBH 3 )(L)(CO) 2 ] [M = Mo and L = ethane-1,2-diamine (en) or bipyridine (bipy); M = Wand L = en, bipy or 1,2-bis(diphenylphosphanyl)ethane (dppe); Liu et al, 2008]. In all these cases, the cyanotrihydridoborate ligand coordinates through the N atom (M-NCBH 3 ), but the isomeric form M-CNBH 3 is also known, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The same workers (6) have also found that the nature of the product depends largely upon the metal and the phosphine ligand. For example, sometimes only hydrido complexes are obtained.…”
Section: Introductionmentioning
confidence: 90%
“…indicative of an N-bonded BH,CN grouping (3,6). For comparison with this and other compounds reported in this paper, i.r.…”
Section: Dbpmentioning
confidence: 99%
“…4) which occur at >2400 cm-', and involve double hydrogen bridges (13,14). Compounds containing monodentate BH, have been shown (15) to have ir bands at -2400-2250 cm-' and bands at -2380 cm-' have been observed (3) in the tetrahedral complex Co(BH,)(PPh,),.…”
Section: Reactions Of Ru(ii) Carbonyl Chloride Solutionsmentioning
confidence: 99%